Electrocardiography terminal - Infante Vazquez, O.; Rodriguez Rossini, G.; Pérez Ruíz, J.; Espinoza, L.; Valenzuela, F.; Rojas Villanueva, M. (Revista Mexicana de Ingenieria Biomedica, 1988)
We present a system based on a PC microcomputer that allows monitoring the electrocardiogram and heart rate. Preserving the characteristics of conventional systems such as selecting alarm levels for high and low frequency and freezing and storing some portion of the ECG. It can be measured, operated arithmetically, derived, integrated or smoothed; can also be sent to printer, graph or to another ECG terminal via modem and in this way exchange of information by text.